2018
DOI: 10.1093/ndt/gfx362
|View full text |Cite
|
Sign up to set email alerts
|

Bone disease in nephropathic cystinosis is related to cystinosin-induced osteoclastic dysfunction

Abstract: CTNS is required for proper osteoclastic activity. In vitro low doses of cysteamine have beneficial antiresorptive effects on healthy human-derived OCs and may partly correct the CTNS-induced osteoclastic dysfunction in patients with NC. Moreover, in vitro low doses of cysteamine also stimulate osteoblastic differentiation and mineralization, with an inhibitory effect at higher doses, likely explaining, at least partly, the bone toxicity observed in patients receiving high doses of cysteamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 11 publications
4
27
1
Order By: Relevance
“…Another proposed mechanism of skeletal damage is cysteamine toxicity. This hypothesis is based on recent in vitro evidence which shows that high doses of cysteamine may inhibit osteoblastic proliferation, and on the fact that cysteamine binds copper, a cofactor for lysyl oxidase, an enzyme that generates the aldehydes required for collagen crosslinking . We observed that cystine levels were not associated with BMD Z ‐scores, although all subjects in our NIH cohort were receiving cysteamine treatment at time of evaluation, eliminating our ability to compare the frequency of skeletal complications between treated and untreated groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another proposed mechanism of skeletal damage is cysteamine toxicity. This hypothesis is based on recent in vitro evidence which shows that high doses of cysteamine may inhibit osteoblastic proliferation, and on the fact that cysteamine binds copper, a cofactor for lysyl oxidase, an enzyme that generates the aldehydes required for collagen crosslinking . We observed that cystine levels were not associated with BMD Z ‐scores, although all subjects in our NIH cohort were receiving cysteamine treatment at time of evaluation, eliminating our ability to compare the frequency of skeletal complications between treated and untreated groups.…”
Section: Discussionmentioning
confidence: 97%
“…There are several other mechanisms that could contribute to the high frequency of decreased bone mass and incidental fractures in nephropathic cystinosis. CTNS is expressed in osteoblasts and osteoclasts, and it has been suggested that mutations in this gene can impair the ability of bone marrow stromal cells to differentiate into osteoblasts. Cysteamine treatment may restore this ability, and additionally have beneficial antiresorptive effects by partly correcting the CTNS‐induced osteoclastic dysfunction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, low doses of cysteamine in vitro stimulate osteoblastic differentiation and mineralization, with an inhibitory effect at higher doses, possibly explaining the bone toxicity observed in patients receiving high doses of cysteamine. Cystinosin may also be required for proper osteoclastic and osteoblastic activity …”
Section: Cystinosis Metabolic Bone Diseasementioning
confidence: 99%
“…Cystinosin may also be required for proper osteoclastic and osteoblastic activity. 35,36 3.3 | Assessing CMBD Serum mineral and enzyme values provide measures of bone health in both children and adults with cystinosis ( Table 2). In children with hypophosphatemic rickets, serum phosphate, bicarbonate, and potassium reflect renal losses and the efficacy of replacement therapy, and alkaline phosphatase (ALP) is a biomarker of rickets and osteomalacia.…”
Section: Pathogenesis Of Cmbdmentioning
confidence: 99%